PERBEDAAN PENGGUNAAN BIOSLURRY DAN PUPUK KOMERSIAL PADA TANAMAN PAKAN RUMPUT PAKCHONG - winurdana, alfan setya; rahmawati, resti yuliana (Jurnal Peternakan (Jurnal of Animal Science), 2025)
This study aimed to evaluate the effect of bioslurry and NPK fertilizer on the growth of elephant grass (Pennisetum purpureum cv Thailand), focusing on two key parameters: fresh weight and dry weight. The research was conducted over a period of two months, with two treatments: P1: bioslurry 75 L/ha and P2: NPK 300 kg/ha, each replicated five times. The results showed that the fresh weight of plants in the bioslurry treatment was 5.95 kg, while the NPK treatment produced 5.89 kg. For dry weight, bioslurry resulted in 1.21 kg, slightly higher than NPK, which produced 1.18 kg. Although the differences between the two treatments were minor, bioslurry showed a slightly better performance in supporting the growth of elephant grass. Bioslurry, being an organic fertilizer, not only provides essential nutrients (N, P, K) but also improves soil structure and increases water retention, which is vital for plant growth. On the other hand, NPK fertilizer provides nutrients rapidly but does not contribute to long-term soil improvement. These findings suggest that bioslurry can be a more sustainable alternative to chemical fertilizers, enhancing soil quality and supporting sustainable agriculture.